Encounters with Gendered Realities in Career Decision-making While Scouting Women Participation in the Indian Workforce. Issue 2 (July 2019) - Tiwari, Himanshi
Abstract: Participation of women in the workforce is crucial for any economy to optimally utilize the potential of its full human capital. However, according to the Global Gender Gap Report (2016) by World Economic Forum, no country by now has achieved gender equality. Due to demographic change as well as a stronger focus on service and knowledge-intensive industries, India will face a significant shortage of (qualified) skills in the next decades. To secure qualified labor, it will be of vital importance for large companies to diversify the pool of (potential) employees by gaining better access to the female labor force. When a pool of young women, who are professionally qualified to participate in the workforce and contribute to the country, cannot utilize their true talent, it becomes quite important to know and understand the reasons for that. Career choice and career decisions of women are influenced by a number of social, cultural, familial, and personal factors. The article seeks to identify the reasons of decreased female participation in the Indian workforce from the lenses of career theories and practicalities of career decision-making. It is aimed at a focused target group, that is, young women (between the age of 25 and 45) who have full-time enrollment in university education, are professionally qualified to join the workforce, and are living in an urban setting, yet not contributing in the workforce.